Lee Harvey Oswald as I knew him - Mohrenschildt, George de (University Press of Kansas, 2014)
""Let us hope that this book, poorly written and disjointed, but sincere, will help to clear up our relationship with our dear, dead friend Lee."" Thus concludes a largely forgotten manuscript appended to Volume XII of the House Select Committee on Assassinations. ""Lee, "" of course, was Lee Harvey Oswald, the man accused of having assassinated President John F. Kennedy in Dallas on November 22, 1963-and whose closest friend, many have argued, was Dallas resident George de Mohrenschildt. For years following Kennedy's assassination there were rumors and assumptions-some started by de Mohrenschil